23.7k views
1 vote
Solve for b.

-9/3 + b = -1
b =

User Chamanhm
by
4.9k points

2 Answers

1 vote

Answer:

b=2

Explanation:

You need to simplify as much as you can before doing anything else.

You can simplify -9/3 to -3! You’re dividing a negative by a positive, which means the answer for that will still be negative.

Now, you have -3+b=-1. Subtract -3. But, you’re subtracting a negative, which means you’ll be adding a positive! So, you’re doing -1 + 3. That gets you 2.

So, b= 2.

:)

User Petra
by
5.2k points
3 votes

Let's solve your equation step-by-step.

-9 ÷ 3 + b = -1

Step 1: Simplify both sides of the equation.

−9

3

+b=−1

−3+b=−1

b−3=−1

Step 2: Add 3 to both sides.

b−3+3=−1+3

b=2

Answer:

b=2

User Davidbelow
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.